Early life adversity alters normal sex-dependent developmental dynamics of DNA methylation. (30th September 2016) - Massart, Renaud; Nemoda, Zsofia; Suderman, Matthew J.; Sutti, Sheila; Ruggiero, Angela M.; Dettmer, Amanda M.; Suomi, Stephen J.; Szyf, Moshe
Abstract: Studies in rodents, nonhuman primates, and humans suggest that epigenetic processes mediate between early life experiences and adult phenotype. However, the normal evolution of epigenetic programs during child development, the effect of sex, and the impact of early life adversity on these trajectories are not well understood. This study mapped the genome-wide DNA methylation changes in CD3+ T lymphocytes from rhesus monkeys from postnatal day 14 through 2 years of age in both males and females and determined the impact of maternal deprivation on the DNA methylation profile. We show here that DNA methylation profiles evolve from birth to adolescence and are sex dependent. DNA methylation changes accompany imposed weaning, attenuating the difference between males and females. Maternal separation at birth alters the normal evolution of DNA methylation profiles and targets genes that are also affected by a later stage maternal separation, that is, weaning. Our results suggest that early life events dynamically interfere with the normal developmental evolution of the DNA methylation profile and that these changes are highly effected by sex.